Human milk: an invisible food resource - Hatløy, Anne; Oshaug, Arne (International Food Policy Research Institute, 1997)
Human milk is a food that meets all conditions for an infant's nutrition security and is the most important food for more than 10 percent of the population in Sub-Saharan Africa (children less than three years of age). Statistics on production of human milk at local and national levels are lacking for Africa. In this paper, the quantity of human milk production in Mali, Senegal, Nigeria, and Zimbabwe is estimated. The annual production in the urban and rural areas in a county in Mali is estimated at 13 and 17 kilograms per capita, respectively. National annual median production is estimated to be between 144,000 (Mali) and 1.3 million metric tons (Nigeria), and production per capita between 8 (Zimbabwe) and 15 kilograms per year (Mali). In Sub-Saharan Africa, the production of human milk is about 50 percent of that of cow's milk. The paper argues that overlooking human milk production/consumption in data analysis and policymaking has negative consequences for children's health and nutritional status.